2010
DOI: 10.1590/s0100-40422010000800012
|View full text |Cite
|
Sign up to set email alerts
|

Validação de método para a determinação de 5-hidroximetilfurfural em mel por cromatografia líquida e sua influência na qualidade do produto

Abstract: Recebido em 16/11/09; aceito em 9/4/10; publicado na web em 24/8/10 METHOD VALIDATION TO HMF DETERMINATION IN HONEY BY HPLC-UV AND ITS INFLUENCE ON THE PRODUCT QUALITY. In honey 5-hydroxymethyl-2-furaldehyde (HMF) is one of the most typical products of degradation: it is usually absent in fresh honey, but its concentration tends to rise as a result of heating processes or long-term storage. The validation protocol was performed in terms of detection and quantification limits, precision (by repeatability and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…Cane syrups were characterized by lower amounts of HMF (109.2 -893.1 mg kg -1 ) ( Table 3) and so as observed above for corn syrup, the concentrations of this contaminant found in Brazilian samples were higher than that reported in literature (100 -300 mg kg -1 ) (Kowalski, Lukasiewicz, Duda-Chodak, & Zieć, 2013). Differences in HMF concentrations of cane and corn syrups can be explained considering several factors that promote the formation this contaminant in foods (thermal processing involving high temperatures, long storage times and food chemical composition) (Capuano & Fogliano 2011;Spano et al, 2009;Lemos et al, 2010;Vorlová et al, 2006;Toker, Dogan, Ersöz, & Yilmaz, 2013).…”
Section: Tablesupporting
confidence: 49%
See 2 more Smart Citations
“…Cane syrups were characterized by lower amounts of HMF (109.2 -893.1 mg kg -1 ) ( Table 3) and so as observed above for corn syrup, the concentrations of this contaminant found in Brazilian samples were higher than that reported in literature (100 -300 mg kg -1 ) (Kowalski, Lukasiewicz, Duda-Chodak, & Zieć, 2013). Differences in HMF concentrations of cane and corn syrups can be explained considering several factors that promote the formation this contaminant in foods (thermal processing involving high temperatures, long storage times and food chemical composition) (Capuano & Fogliano 2011;Spano et al, 2009;Lemos et al, 2010;Vorlová et al, 2006;Toker, Dogan, Ersöz, & Yilmaz, 2013).…”
Section: Tablesupporting
confidence: 49%
“…Initially the chromatographic conditions reported by Lemos et al (2010) for HMF analysis in honey samples using water:acetonitrile (80:20, v/v) as mobile phase with flow rate of 1.0 mL min -1 were tested for the cane syrup sample (CS1). In the chromatogram for this mobile phase it was observed that the peaks were not well separated (resolution < 1.5).…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…O aumento progressivo na quantidade de moléculas de HMF ocorre naturalmente com o envelhecimento do mel, sendo que, a reação de formação do composto é potencializada pela elevada concentração de íons hidrônios, geralmente méis de meliponíneos apresentam uma concentração hidrogenionica superior aos méis de Apis, que desestabiliza a frutose gerando o HMF. Outros fatores como a umidade, estresse fotoquímico e origem botânica podem afetar a produção de HMF (KHALIL, SULAIMAN & GAN, 2010;LEMOS, SANTOS & SANTOS, 2010). Gidamis et al (2004) armazenaram o mel de Apis durante sete meses (intervalo de um mês) e observaram o aumento na formação do HMF com o tempo de armazenamento.…”
Section: Qualquerunclassified
“…The use of biodiesel increases every year, and it is forecast that in 2020 biodiesel production will be nearly 36.9 million metric tons, 10 million metric tons more than the current production. Therefore, for the success of the biodiesel production chain, it is essential to find pathways to use or consume glycerol [6,7]. Due to its non-toxicity, glycerol has many commercial applications, such as in the manufacture of medicines, foods, beverages, and textiles [8].…”
Section: Introductionmentioning
confidence: 99%